The Discrete System and Its Models for Digital Signal Processors - Smekal, Z. (Společnost pro radioelektronické inženýrství, 1993)
The discrete system is mostly described with the help of the system transfer function and the zero input response is usually neglected. In this paper the state-space equations express the total response of the discrete system, and they are arranged to a digital signal processor implementation.
Keywords: LTI discrete system; signal flow graphs; canonic forms; digital signal processor